Participatory planning of the future of waste management in small island developing states to deliver on the Sustainable Development Goals - Fuldauer, L; Ives, M; Adshead, D; Thacker, S; Hall, J (Elsevier, 2019)
Waste management is particularly challenging for Small Island Developing States (SIDS) due to their high per-capita infrastructure costs, remoteness, narrow resource bases and high dependence on tourism. The lack of integrated planning frameworks considering these SIDS-characteristics has stalled progress on sustainable waste management. To address this challenge, this paper proposes an integrated methodology for long-term waste management planning to deliver on the United Nations’ Sustainable Development Goals (SDGs) in SIDS. This explicitly combines multi-level participatory SDG visioning and back-casting with waste infrastructure modelling. This methodological development is piloted using a national-scale demonstration on Curacao. Three island-specific waste management portfolios (Inaction, Circular Economy, Technology-led), developed through stakeholder back-casting, are modelled for SDG delivery using a national accounting model under different socio-economic futures. The results highlight the importance of waste prevention and material re-use strategies within islands that engage local populations. Evidence-based identification and evaluation of waste management strategies, grounded in participatory processes, can itself contribute to SDG delivery.